Effects of S906T polymorphism on the severity of a novel borderline mutation I692M in Nav1.4 cause periodic paralysis. Issue 6 (24th November 2016) - Fan, C.; Mao, N.; Lehmann‐Horn, F.; Bürmann, J.; Jurkat‐Rott, K.
Abstract : Hyperkalemic periodic paralysis (HyperPP) is a dominantly inherited muscle disease caused by mutations in SCN4A gene encoding skeletal muscle voltage gated Na v 1.4 channels. We identified a novel Na v 1.4 mutation I692M in 14 families out of the 104 genetically identified HyperPP families in the Neuromuscular Centre Ulm and is therefore as frequent as I693T (13 families out of 14 HyperPP families) in Germany. Surprisingly, in 13 families, a known polymorphism S906T was also present. It was on the affected allele in at least 10 families compatible with a possible founder effect in central Europe. All affected members suffered from episodic weakness; myotonia was also common. Compared with I692M patients, I692M‐S906T patients had longer weakness episodes, more affected muscles, CK elevation and presence of permanent weakness. Electrophysiological investigation showed that both mutants had incomplete slow inactivation and a hyperpolarizing shift of activation which contribute to membrane depolarization and weakness. Additionally, I692M‐S906T significantly enhanced close‐state fast inactivation compared with I692M alone, suggesting a higher proportion of inactivated I692M‐S906T channels upon membrane depolarization which may facilitate the initiation of weakness episodes and therefore clinical manifestation. Our results suggest that polymorphism S906T has effects on the clinical phenotypic and electrophysiological severity of a novel borderline Na v 1.4 mutation I692M, making the borderline mutation fully penetrant. Abstract :